2021
DOI: 10.1002/celc.202100768
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO‐Modified Polymethacrylates as Mediators in Electrosynthesis – Redox Behavior and Electrocatalytic Activity toward Alcohol Substrates

Abstract: Homogeneous catalysts (“mediators”) are useful for tuning selectivity in organic electrosynthesis. However, they can have a negative impact on the overall mass and energy balance if used only once or recycled inefficiently. In a previous work, we introduced the polymediator concept, in which soluble redox‐active polymers catalyze the electrochemical reaction, allowing for recovery by dialysis or pressure‐driven membrane filtration. Using anodic alcohol oxidation as a test case, it was shown that TEMPO‐modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 50 publications
4
14
0
Order By: Relevance
“…UV-vis spectroscopic studies confirmed that PTM • HCl initially contains intact thiobenzoylthio end groups, which are cleaved off during reaction to TPMA. [13] End group removal under alkaline and oxidative conditions is also in agreement with literature reports on the stability of thiobenzoylthio moieties. [21] Further details on preparation, purification, and characterization of the polymers are provided in the Supporting Information.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…UV-vis spectroscopic studies confirmed that PTM • HCl initially contains intact thiobenzoylthio end groups, which are cleaved off during reaction to TPMA. [13] End group removal under alkaline and oxidative conditions is also in agreement with literature reports on the stability of thiobenzoylthio moieties. [21] Further details on preparation, purification, and characterization of the polymers are provided in the Supporting Information.…”
Section: Resultssupporting
confidence: 88%
“…Concept of indirect electrolysis using polymediators and polyelectrolytes. [12,13] A) Preparative-scale anodic oxidation of alcohols using polymediators (TPMA) and polyelectrolytes (PTE). [12] B) Polyelectrolyte and Noxyls under investigation in previous works.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations